Use of a Yeast Protein-Based Intumescent Fire Retardant Bioadditive as Thermal and Mechanical Reinforcement for a PVAc Adhesive for Wood Products - Marcela Vidal-Vega; Mario Núñez-Decap; Diógenes Hernández-Espinoza; Arturo Fernández-Pérez (Applied Sciences)
In this study, an intumescent fire retardant (IFR) bioadditive was designed based on a commercial Saccharomyces cerevisiae yeast protein matrix. Lignosulfonate was used as a cohesive reinforcement of its polymeric structure, along with magnesium hydroxide Mg(OH)2, as agents that enhance the binder-intumescent properties, with the aim of improving the thermal stability and fire resistance of the commercial PVAc adhesive. Firstly, two formulations of the bioadditive were elaborated and characterized for their physicochemical and electrical properties, dynamic mechanical analysis (DMA), adherence properties (shear strength), and fire resistance, to modify the PVAc adhesive. Thus, it was found that the IFR bioadditive formulation with a higher percentage of Mg(OH)2 was more thermally stable than the other one, although both of them were able to enhance the binder-intumescent properties of the commercial adhesive PVAc. Then, ten adhesive blends of PVAc modified with these two different bioadditives were added in different proportions, and were elaborated and characterized for their physicochemical and electrical properties, mechanical properties including a shear test (dry, elevated temperature, and three-cycle conditions) and delamination. Based on these results, five adhesive blends were selected, and we performed the following tests: adhesive penetration, fire resistance, volatile organic compounds (VOCs), and morphological and elemental analysis by scanning electron microscope (SEM/EDS). From the modified PVAc adhesive blends, two samples were selected, which were able to improve the high temperature and fire performance of a PVAc adhesive.